Analysis of the Physical Condition of Pencak Silat Athletes from KORMI PSN Perisai Putih Jambi City Heading to FORNAS 2025 - Ayu Wandira; Muhammad Ali; Grafitte Dechelin (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
The purpose of this study was to determine the Physical Condition of KORMI PSN Perisai Putih Pencak Silat Branch Athletes in Jambi City Towards FORNAS 2025. The type of research in this study is descriptive quantitative with data collection techniques using tests and measurements. The population studied in this study were athletes of the KORMI PSN Perisai Putih Pencak Silat branch of Jambi City, with a total of 6 people including 2 men and 4 women. Total sampling technique. This research was conducted at SMP N 14 Jambi City. Research time was held on February 3-8, 2025. This type of research is descriptive quantitative with data collection techniques using tests and measurements. The physical condition instruments used are: speed (30 meter sprint), flexibility (sit and reach) strength (push up), agility (hexogon obstacle), Power (standing board jump), Endurance (bleep test). Based on data analysis, it is obtained that the physical condition of the speed test for 1 Putra has a category of less, 1 male is categorized as less and 1 person is categorized as less, 3 people are categorized as very less. 1 Putra's flexibility has a category of enough, 1 male is categorized as less and 3 people are categorized as less, 1 person is categorized as very less. Strength 1 Male has a sufficient category, 1 male is categorized as less and 1 person is categorized as sufficient, 2 people are categorized as less, 1 person is categorized as less. agility 1 Male has a less category, 1 male is categorized as less and 2 people are categorized as less, 2 people are categorized as less. Power 1 Male has a category of less, 1 male is categorized as less and 1 person is categorized as good, 2 people are categorized as sufficient, 1 person is categorized as very less. Endurance 1 Putra has a category of less, 1 male is categorized as very less and 4 people are categorized as very less. It can be concluded that the physical condition of Pencak Silat athletes KORMI PSN Perisai Putih Jambi City 2025, has obtained the results of all test items showing that the level of physical condition of male athletes and female athletes is in the 'less' category.